Age does not modify the effects of treatment on pain in patients with low back pain: secondary analyses of randomized clinical trials - Ferreira, Manuela L.; Ferreira, P. H.; Henschke, Nicholas; Kamper, S. J.; Koes, B.; Hayden, J. A.; Maher, C. G. (European journal of pain, 2014)
Background While many treatment options have been advocated to speed recovery in adults with back pain, it is still unclear whether older patients with back pain respond differently to treatment when compared to younger patients. Aims This study aims to evaluate if age modifies response to treatment in patients with back pain, by conducting secondary analyses of seven randomized clinical trials of common interventions for back pain. Methods Data from 1233 participants were sourced from two randomized clinical trials on patients with acute back pain and five on patients with persistent back pain. Trials were conducted between 2001 and 2010 and assessed conservative treatments for back pain, including exercise, spinal manipulative therapy and anti-inflammatory drugs. Individual participant data analyses were performed using a ‘one-stage’ approach including all available data in a single two-level model, with participants being one level and trials being the second level. Only pain outcomes assessed immediately after treatment were included in the analyses. Results Mean combined age of included participants was 49 years (SD: 15.4). Multivariate fractional polynomial analyses revealed no significant interaction (p > 0.05) between age and treatment effect sizes in patients with low back pain for any of the treatment comparisons. Conclusion These results offer preliminary evidence suggesting that the generally small effects of conservative treatments for low back pain are in fact observed across all age groups.